A 90‐day adaptation to a high glycaemic diet alters postprandial lipid metabolism in non‐obese horses without affecting peripheral insulin sensitivity. Issue 2 (30th November 2011) - Suagee, J. K.; Corl, B. A.; Swyers, K. L.; Smith, T. L.; Flinn, C. D.; Geor, R. J.
Summary High glycaemic feeds are associated with the development of insulin resistance in horses. However, studies that evaluated the effect of high glycaemic feeds used horses that either ranged in body condition from lean to obese or were fed to increase body condition over a period of months; thus, the ability of high glycaemic feeds to induce insulin resistance in lean horses has not been determined. This study evaluated the insulin sensitivity of 18 lean horses fed a 10% (LO; n = 6), 20% (MED; n = 6) or 60% (HI; n = 6) non‐structural carbohydrate complementary feed for 90 days. Although both the MED and HI diets increased insulinaemic responses to concentrate feeding in relation to the LO diet (p > 0.05), neither induced insulin resistance, as assessed by glucose tolerance test, following the 90‐day feeding trial. Interestingly, the post‐feeding suppression of plasma non‐esterified fatty acids was less pronounced in HI‐fed horses (p = 0.054) on days 30 and 90 of the study, potentially indicating that insulin‐induced suppression of adipose tissue lipolysis was reduced. As insulin‐resistant animals often have elevated plasma lipid concentrations, it is possible that altered lipid metabolism is an early event in the development of insulin resistance. The effects of high glycaemic feeds that are fed for a longer duration of time, on glucose and lipid metabolism, should be investigated further.